2022
DOI: 10.1093/her/cyac020
|View full text |Cite
|
Sign up to set email alerts
|

Does public health education improve migrant workers’ health status in China?—evidence from China Migrants Dynamic Survey

Abstract: This study investigates the effect of public health education (PHE) on migrant workers’ health status in China, using the data collected from the China Migrants Dynamic Survey project. The analysis employs a probit model, whose results suggest that, in general, PHE has a statistically significant and positive impact on migrant workers’ self-rated health status and exerts a negative impact on their incidence rate of daily diseases. We also utilize the conditional mixed process method to address the potential en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Predisposing characteristics include gender, age, marital status, and education level ( 44 ). As economic, social environments, and health insurance policies vary across provinces ( 45 ), the study also controls for the province of residence according to related literature ( 46 ). Enabling resources comprise family income level, employment status, and hukou type ( 43 ).…”
Section: Methodsmentioning
confidence: 99%
“…Predisposing characteristics include gender, age, marital status, and education level ( 44 ). As economic, social environments, and health insurance policies vary across provinces ( 45 ), the study also controls for the province of residence according to related literature ( 46 ). Enabling resources comprise family income level, employment status, and hukou type ( 43 ).…”
Section: Methodsmentioning
confidence: 99%
“…Public health education is a crucial aspect of disease prevention and health promotion. It is recognized worldwide as a strategic healthcare measure ( 16 ) and a fundamental component of public services ( 17 ). Effective public health education can improve self-health awareness and health literacy ( 18 ), promote healthy behaviors, and establish correct health concepts ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al analyzed the impact of health education on the health of the mobile population using data from China’s 2017 China Migrant Dynamic Survey. They concluded that compared with those who did not receive public health education, receiving public health education resulted in a 4.1% improvement in self-health, and a reduction in the incidence of daily symptoms and diseases by 5.3 and 6.1% respectively, compared to those who did not receive public health education ( 17 ). Yan et al’s findings also showed that receiving public health education increased the probability of self-assessed health improvement by 5.4–6.1% among the older adult mobile population ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both domestic and international studies have further discovered that human educational capital plays a role in the intergenerational transmission of health entitlements for China's migrant workers. Each additional year of education for migrant workers can raise the probability of their accompanying children obtaining medical insurance, health records and health education by 62.38, 9.92 and 18.11%, respectively (Wang, 2019; Xie et al ., 2020; Li, 2020; Chen et al ., 2020; Zhu, 2021).…”
Section: Introductionmentioning
confidence: 99%